Odious Debt dan Illegitimate Debt dalam Hukum Internasional: Implikasi Terhadap Audit Badan Pemeriksa Keuangan atas Utang Luar Negeri Indonesia: Odious Debt and Illegitimate Debt in International Law: Implications for the Audit of Indonesia’s Foreign Debt by the Audit Board of the Republic of Indonesia - Reninda Dwi Astuti; Pipit Adila Wati; Septiandro Surya Dewangga (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2026)
The launch of the Whoosh Railway has raised discussions regarding the legitimacy of foreign debt (ULN). Since the early days of independence, development in Indonesia has frequently utilized foreign debt funds, a practice exemplified by the Whoosh project. The doctrine of odious debt asserts that debt obligations which are not used for the benefit of the people cannot be charged to the state. This concept is expanded by the illegitimate debt doctrine, which adds the variable of negotiation transparency. This study aims to analyze both the odious debt and illegitimate debt doctrines within the framework of international law and to identify the normative boundaries of the Audit Board's (BPK) authority in auditing foreign debt. A juridical-normative method is chosen to examine the existing positive law. The research approach is conducted through three methods, namely conceptual, comparative, and case-based approaches. Based on the analysis of the Whoosh Train case within the framework of the odious debt and illegitimate debt doctrines, the case is more likely to be classified as illegitimate debt due to procedural flaws in the decision making process. Both doctrines can serve as additional evaluative perspectives for the Supreme Audit Board (BPK) in auditing debt policy, particularly in screening for nontransparent debt. However, neither doctrines is yet sufficient to serve as a legal basis for determining the validity of state debt, given their status as soft law.